Waist-to-Height Ratio as a predictor of cardiovascular and metabolic health in a pediatric population - Per Morten Fredriksen; Asgeir Mamen; Nandu Goswami; Morten Lindberg (PLoS ONE, 2025)
Background Understanding the relationship between central adiposity and health outcomes in children is crucial for early prevention of non-communicable diseases (NCDs). Waist-to-height ratio (WHtR) has emerged as a key anthropometric measure for predicting cardiovascular and metabolic health risks. Methods The objective of this study was to investigate whether WHtR is associated with cardiovascular and metabolic risk markers, including HbA1c, CRP, lipid profiles, blood pressure, ferritin, and iron levels, in healthy children aged 6–12 years. The study further aimed to assess WHtR’s potential as a screening tool for identification of cardiometabolic risk. Results An association between WHtR and unfavorable lipid profiles, with elevated total cholesterol and non-HDL cholesterol levels, alongside decreased HDL levels in the highest WHtR quartile, were displayed, suggesting increased cardiovascular risk. Similarly, the combination of high erythrocyte count, low hematocrit (HCT), high ferritin, and low iron, combined with high CRP may imply chronic inflammation due to adiposities. Elevated systolic and diastolic blood pressure values further underscore this cohort’s cardiovascular risks associated with central adiposity. Conclusion WHtR’s ability to predict metabolic and cardiovascular risk factors highlights its potential as a simple, non-invasive screening tool in pediatric healthcare. Implementing WHtR in routine health assessments could provide an accessible and cost-effective method for early identification of at-risk children, enabling timely interventions to improve long-term health outcomes. Trial registration Clinical Trial.gov. Identifier: NCT02495714. Registered 20 June 2015. https://register.clinicaltrials.gov/prs/app/action/LogoutUser?uid=U0002ORK&ts=13&sid=S0005MCN&cx=pc85td